The reinforcing effects between flying as a core service and partners within a local oyalty programme . - Mosala, Thabo (My University, 2015)
This research replicated a dynamic model of cross-buying across loyalty programme partnerships and tested the model using data from a South African airline. The research sought to identify reinforcing mechanisms active between partners.
MBA Thesis
Keywords: Customer loyalty programs,Airlines -- South Africa -- Management